Perkembangan Bahasa dan Sastra Arab pada Abad Keemasan Islam - Nuraeni Novira; Syarifuddin Ondeng; Andi Abdul Hamzah (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2023)
This research aims to find out how Arabic language and literature developed in the golden age of Islam. This research is library research which is descriptive qualitative in nature, with a historical approach. The problems raised in this research are first: why is it called the golden age of Islam, second, how did Arabic language and literature develop in the Abbasid period, third: what were the characteristics of Arabic literature in the Abbasid era? The results of the research show that: (1) The Abbasid dynasty placed more emphasis on fostering civilization and Islamic culture rather than territorial expansion. At that time, scientific institutions were established as centers for learning science, culture and Islamic education. Especially during the reign of Caliph Harun al-Rasyid and his son al-Makmun. (2) The purification of the Arabic language went smoothly because it was assisted by the attitude and attention of the caliphs and ministers who were in power at that time. The publication of books in Arabic from all fields of science, and the emergence and birth of writers who are experts in the field of language arts, both poetry and prose. Poets competed with each other to please the king by praising his superiors. That's why the rulers also competed with each other in giving gifts and rewards to every poet who presented his poetry to the ruler. (3) Arabic poetry did not appear all at once in perfect form, but little by little developed towards perfection, starting from the absolute form of word expression. (mursal) go to the course' and from the poem to the poem which has a prophecy, then to the poem which has the message Rajaz. Starting from this phase, Arabic poetry is said to be perfect, and over a long period of time the poetry develops into a composition of qashidah which is bound by the endings of wazan and qafiyah.